Why Hoop Tension Matters: A Biomechanical Perspective on Medial Meniscus Posterior Root Tears—A Narrative Review - Man Soo Kim; Yong In; Hyungtae Kim; Juyoung Jeong; Sueen Sohn (Bioengineering)
This narrative review aims to provide an in-depth understanding of the biomechanical consequences of medial meniscus posterior root tears (MMPRTs), with a particular focus on the role of hoop tension in meniscal function. By revisiting fundamental principles such as load transmission, contact mechanics, and structural stabilization, this review elucidates how MMPRTs compromise both the integrity and function of the knee joint. The disruption of hoop tension is analyzed across various tear patterns, and through a synthesis of biomechanical experiments, the superiority and necessity of anatomical structural restoration over conservative management or meniscectomy are emphasized. A comprehensive grasp of these biomechanical foundations offers a critical perspective on the pathomechanics of MMPRTs and serves as a basis for more rational, evidence-based surgical decision-making in clinical practice.